PhD Research on Economics Development Link with Human Resources Management - Shaukat, Iqbal (The Eastasouth Journal of Social Science and Humanities, 2025)
Human resource is the important part of our world. With the help of human resource, we cannot achieve the goal of development in human life. Before some years the human resource department is not important. But in the era of globalization the human resource became the important department. After the scientific revolution the human resource is very important, human resource is very important in this era of globalization. Teconology provide the path how to utilize the resources according to need of time. Human resource management is directly link to human physiology. Human resource management is directly link with the Business management. Human resource management guide us in many areas of human devlopment. Human resource management provide the way how to utilize the human talent according to target. Human resource management study is very important student. Human resouce management are being teaches in every university and business school.